Assessing the Identity of Commercial Herbs From a Cambodian Market Using DNA Barcoding - Cui, Xinyun; Li, Weijie; Wei, Jianhe; Qi, Yaodong; Li, Rongtao; Yang, Yun; Shi, Yuhua; Meng, Xiangxiao; Mi, Yaolei; Huot, Theang; Sun, Wei; Zheng, Xilong (Frontiers in Pharmacology, 2020)
In Cambodia, medicinal plants are often used to treat various illnesses. However, the identities of many medicinal plants remain unknown. In this study, we collected 50 types of traditional Cambodian medicinal plants that could not be identified by their appearance from a domestic market. We utilized the DNA barcoding technique, combined with the literature survey, to trace their identities. In the end, 33 species were identified at the species level and 7 species were identified at the genus level. The ethnopharmacological information of 33 medicinal plants was documented. The DNA barcoding technique is useful in the identification of medicinal plants with no previous information.